A Model of the "Managerial" Enterprise - Marris, Robin (Quarterly Journal of Economics, 1963)
Managerial utility, 186. — Methods and definitions, 191. — Growth rate of demand, 193. — Imitative products, 197. — The supply of finance, 199. — The rate of profit, 200. — Completion, 202. — Interpretation, 204. — Maximizing versus satisficing, 207.